PERENCANAAN PENGADAAN BAHAN PUSTAKA DI SMA NEGERI 4 KARAWANG - Sayan Suryana; Ferianto (LP2M IAIN Sultan Amai Gorontalo, 2023)
This study aims to describe the planning for procurement of library materials in the Karawang 4 Public High School library and what are the factors that influence it. Researchers used descriptive qualitative research. In this study, the information in this study was the head of the library, librarians and users. The data collection techniques in this study were through observation, interviews and documentation. The data analysis technique of this research uses Miles and Huberman analysis which divides the analysis into data collection, data reduction, data display and conclusion drawing, verification. The results of this study indicate that the planning process for procuring library materials begins with determining the budget, then selecting library materials up to the purchasing process, the methods used in procuring library materials at SMA Negeri 4 Karawang are, 1) Purchases, 2) Gifts, and 3) donations . The supporting factors for planning the procurement of library materials in the SMA Negeri 4 Karawang library are, 1) There is assistance from outside parties, both agencies or individuals who contribute in the form of books to add to the collection of library materials, and 2) The planning system for procuring library materials is already going well . While the inhibiting factors are 1) Lack of competence of managers in properly managing the procurement of library materials. Keywords: Planning, Procurement, Library Materials